Development Of Rural Tourism-Based Biology Learning Devices In Pentingsari Village Cangkringan Yogyakarta - Sekar Jati Pamungkas; I Gusti Putu Suryadarma (Indonesian Journal of Biology Education, 2018)
This study aims to develop rural tourism-based biology learning devices based on 4-D models. The research on the development of rural tourism-based biology learning devices uses 4-D model (defines, design, develop, and disseminate) proposed by Thiagarajan. The results show that this study generates rural tourism-based biology learning devices based on a 4-D model.